The Linkage of Serial Cyclone Clustering in Western Europe and Weather Regimes in the North Atlantic‐European Region in Boreal Winter - Hauser, Seraphine; Mueller, Sebastian; Chen, Xiaoyang; Chen, Ting‐Chen; Pinto, Joaquim G.; Grams, Christian M.; 1 Department Troposphere Research (IMK‐TRO) Institute of Meteorology and Climate Research Karlsruhe Institute of Technology (KIT) Karlsruhe Germany (Geophysical Research Letters, 2023)
Extra‐tropical cyclones are an important source of weather variability in the mid‐latitudes. Multiple occurrences in a short period of time at a particular location are denominated serial cyclone clustering (SCC), and potentially lead to large societal impacts. We investigate the relationship between SCC affecting Western Europe and large‐scale weather regimes (WRs) in the North Atlantic‐European region in boreal winter. We find that SCC in low latitudes (45°N) is predominantly associated with the anticyclonic Greenland Blocking WR. In contrast, SCC in mid and high latitudes (55°N, 65°N) is mostly linked to different cyclonic WRs. Thereby, SCC occurs typically within a well‐established WR that builds up prior to SCC and decays after SCC. Thus, SCC events are closely associated with recurrent, quasi‐stationary and persistent large‐scale flow patterns (WRs). This mutual relationship reveals the potential of WRs in forecasting storm series and associated impacts on sub‐seasonal to seasonal time scales. Plain Language Summary: Serial cyclone clustering describes the occurrence of multiple extra‐tropical cyclones within a certain time frame and a spatially restricted region. Since extra‐tropical cyclones can be associated with strong winds and heavy precipitation, multiple occurrences can lead to large cumulative impacts in the affected areas. We analyze the relationship between serial cyclone clustering (SCC) in Western Europe and so‐called weather regimes (WRs) in the North Atlantic‐European region in boreal winter. These regimes describe slow evolving and enduring large‐scale atmospheric circulation patterns. Relationships with certain regime types are identified but depend on the latitude at which the clustered frequency of extra‐tropical cyclones is found. When SCC occurs in low latitudes (45°N), it mostly appears coincident with anticyclonic large‐scale flow patterns. In contrast, SCC in mid and high latitudes (55°N, 65°N) often occurs simultaneously with different cyclonic regimes. We find that periods of ...